Geoecological characteristics of spring stows West Kazakhstan region (Journal of Geography and Environmental Management, 2019)
The article provides results of the study of 15 of spring natural boundaries in West Kazakhstan region,including field survey data, chemical and toxicological analysis of water in springs.